Legal Regulation of Power Decentralization in Ukraine: Comparative Analysis and Criminal-Administrative Aspect - Anatolii Rusetskyi; Natalia Blazhivska; Olena Kostenko; Maksym Korniienko; Olexander Krupytskyi (Magister of Law, Faculty of Law, University of Mataram, 2023)
The purpose of this article is to shed light on the decentralization of power reform in Ukraine under war conditions. In the concept of Ukrainian territorial communities, the ancient European traditions of Ukrainian local self-government and modern standards of the European Union are successfully embodied. The article is a qualitative study with a historical and comparative approach. The results of the study conclude that the effective interaction between citizens, the state and international organizations contributed to the formation of Ukrainian territorial communities. It has been shown that personal income tax is one of the main sources of replenishing the budget of the community. In the first nine months of 2022, the local budget in the Dnipropetrovsk region of Ukraine collected 16,364,124 Ukrainian hryvnia (UAH) in personal income tax, which is 34% more than in the same period of 2021. Stabilizing and restoring local self-government in Ukraine requires the introduction of a new, effective and transparent strategic planning system at three levels: state strategy - regional strategy - community strategy. To restore and stimulate regional development, the strategy development must include the identification of the following four types of functional territories: recovery territories, economic growth poles, territories with special development conditions, and territories of sustainable development.